Immunocytochemical profiles of inferior colliculus neurons in the rat and their changes with aging - Ouda, Ladislav; Syka, Josef (Frontiers in Neural Circuits, 2012)
The inferior colliculus (IC) plays a strategic role in the central auditory system in relaying and processing acoustical information, and therefore its age-related changes may significantly influence the quality of the auditory function. A very complex processing of acoustical stimuli occurs in the IC, as supported also by the fact that the rat IC contains more neurons than all other subcortical auditory structures combined. GABAergic neurons, which predominantly co-express parvalbumin (PV), are present in the central nucleus of the IC in large numbers and to a lesser extent in the dorsal and external/lateral cortices of the IC. On the other hand, calbindin (CB) and calretinin (CR) are prevalent in the dorsal and external cortices of the IC, with only a few positive neurons in the central nucleus. The relationship between CB and CR expression in the IC and any neurotransmitter system has not yet been well established, but the distribution and morphology of the immunoreactive neurons suggest that they are at least partially non-GABAergic cells. The expression of glutamate decarboxylase (GAD) (a key enzyme for GABA synthesis) and calcium binding proteins (CBPs) in the IC of rats undergoes pronounced changes with aging that involve mostly a decline in protein expression and a decline in the number of immunoreactive neurons. Similar age-related changes in GAD, CB, and CR expression are present in the IC of two rat strains with differently preserved inner ear function up to late senescence (Long-Evans and Fischer 344), which suggests that these changes do not depend exclusively on peripheral deafferentation but are, at least partially, of central origin. These changes may be associated with the age-related deterioration in the processing of the temporal parameters of acoustical stimuli, which is not correlated with hearing threshold shifts, and therefore may contribute to central presbycusis.